2002
DOI: 10.1021/ma011684d
|View full text |Cite
|
Sign up to set email alerts
|

Probing by Time-Resolved FTIR Spectroscopy Mass Transport, Molecular Interactions, and Conformational Ordering in the System Chloroform−Syndiotactic Polystyrene

Abstract: The transport of chloroform in films of semicrystalline syndiotactic polystyrene (s-PS) in its nanoporous form (δ-form) has been investigated by gravimetric analysis and time-resolved FTIR spectroscopy. Experimental tests have been performed at 56 °C and at several vapor pressures ranging from 5 to 100 Torr. Sorption and desorption kinetics have been monitored with both techniques, and the dependence of diffusion coefficients with penetrant concentration was investigated, evidencing Fickian features typical of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 36 publications
4
46
2
Order By: Relevance
“…Several FTIR studies [43,46,74,75] have given information about the nature of host-guest interactions in s-PS co-crystals.…”
Section: Nature Of the Host-guest Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several FTIR studies [43,46,74,75] have given information about the nature of host-guest interactions in s-PS co-crystals.…”
Section: Nature Of the Host-guest Interactionsmentioning
confidence: 99%
“…It presents two identical cavities and eight styrene monomeric units per unit cell [16] and rapidly and selectively absorbs low-molecular-mass guest molecules even at very low activities, producing clathrate [28][29][30][31][32][33] and intercalate [34][35][36][37] co-crystals. Several recent studies have shown that the d crystalline phase is promising for applications in chemical separations [38][39][40][41] and air/water purification [42][43][44][45][46][47][48][49][50] as well as in sensorics [51][52][53][54][55][56]. It has been also found that the self-assembling of this polymeric framework and active guest molecules into co-crystals reduce guest diffusivity and prevent guest self-aggregation (without recurring to chemical reactions).…”
Section: Introductionmentioning
confidence: 97%
“…21 However, we should be careful when comparing diffusion coefficients obtained under different experimental conditions as suggested by Musto et al 36 The diffusion of penetrant in the amorphous region is greatly influenced by the plasticizing effect. Therefore, the D a depends significantly on the kind and concentration of penetrant.…”
Section: Estimation Of Diffusion Coefficientsmentioning
confidence: 99%
“…Estimation of crystallinity of the δ-form complex is very difficult and only a few papers 17,22 have been reported the crystallinity. In the present study, we calculated approximate crystallinity of the δ-form complex (χ c δ ) as,…”
Section: Resultsmentioning
confidence: 99%